Transcriptomic analysis and comparative characterization of rat H9C2, human AC16 and murine HL-1 cardiac cell lines. (10th June 2022) - Gulyas-Onodi, Z; Visnovitz, T; Koncz, A; Varadi, B; Agg, B; Kiss, B; Makkos, A; Nagy, NR; Toth, VE; Leszek, P; Gorbe, A; Giricz, Z; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme National Research, Development and Innovation Fund of Hungary Background: Cardiac cell lines and primary cell cultures are widely used to model various cardiovascular diseases in vitro. Despite the increasing number of publications using these models, limitations of these cell lines are still undetermined. Purpose: The aim of our study was to compare the most commonly used cardiac cell lines to primary cultures and to mature cardiac tissues by transcriptomic analysis and morphological characterization. Methods: H9C2 (rat), AC16 (human) and HL-1 (mouse) cardiac cell lines were differentiated towards a phenotype more resembling cardiomyocytes, by methods most widely used in the literature, and cells were harvested at stages of proliferation and differentiation. Whole left ventricular tissue, neonatal primary cardiac myocytes isolated from mice and rats, or human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) were applied as references. Transcriptome analysis and immunocytochemical detection of cardiac structural proteins were performed on all cell models. Results: RNA expression of cardiac markers (e.g. Tnnt2, Ryr2, Tnni3) was markedly lower in cell lines compared to primary cells or hiPSC-CM and adult tissue controls. Differentiation procedures induced a significant increase in cardiac- and decrease in embryonic markers in AC16 and H9C2 lines; however, the overall expression pattern of investigated genes in all cell lines showed significant differences in comparison to corresponding myocardium or primary cultures. Immunocytochemistry confirmed low expressions of structural protein alpha-actinin and troponin I in cell lines. Conclusion: Expression patterns of cardiomyocyte markers and mRNA profile indicates low-to-moderate similarity of cell lines to primary cells/cardiac tissues regardless the differentiation protocol used. These limitations should be taken into account while choosing cells as in vitro platforms to model cardiomyocytes and cardiovascular diseases.